2016
DOI: 10.1016/j.jsb.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

ICON: 3D reconstruction with ‘missing-information’ restoration in biological electron tomography

Abstract: Electron tomography (ET) plays an important role in revealing biological structures, ranging from macromolecular to subcellular scale. Due to limited tilt angles, ET reconstruction always suffers from the 'missing wedge' artifacts, thus severely weakens the further biological interpretation. In this work, we developed an algorithm called Iterative Compressed-sensing Optimized Non-uniform fast Fourier transform reconstruction (ICON) based on the theory of compressed-sensing and the assumption of sparsity of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 40 publications
0
84
0
Order By: Relevance
“…2016). Here, the −0.29° tilt (the minimum tilt) projection was excluded as the omit-projection (“ground truth”) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2016). Here, the −0.29° tilt (the minimum tilt) projection was excluded as the omit-projection (“ground truth”) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2016):Step 1Pre-processing. Align tilt series and correct contrast transfer function (CTF).Step 2Gray value adjustment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the contrast and quality of ET reconstruction, they developed three different reconstruction algorithms: ASART, 23 FIRT, 24 and ICON. 25 Notably, ICON combines both nonuniform fast Fourier transformation and compressed sensing techniques and significantly recovers the missing information in both the angular intervals and the missing wedge.…”
Section: Em Methodology and Technologymentioning
confidence: 99%
“…Variations of this method have also been demonstrated for cryoET specimens (Aganj et al 2007; Song et al 2012). Recently, the iterative compressed-sensing optimized non-uniform (ICON) reconstruction (Deng et al 2016) method demonstrated that CS can restore missing information in noisy cryoET data of both cells and isolated macromolecules, thereby minimizing missing wedge artifacts and yielding measurably better reconstructions than WBP.…”
Section: Challenges In Single Particle Tomographymentioning
confidence: 99%